Monitoring Perubahan Areal Persawahan Menggunakan Aplikasi Sistem Informasi Geografis (Studi Kasus: Kecamatan Pallangga Kabupaten Gowa) - Magfirah Djamaluddin; Andi Ramlan; Muh. Jayadi (Universitas Hasanuddin, 2019)
The area of agricultural land, especially paddy fields, is related to the level of rice production. Conversion of agricultural land to non-agriculture will have an impact on the availability of rice supply. This study aims to identify changes in paddy field land use in 2005 - 2016 using high-resolution satellite imagery and calculate the need for rice per capita in Pallangga District. This research utilizes the application of geographic information systems in monitoring changes in paddy field use. The method used in the classification of land use is digitizing on screen. The conversion of paddy fields to non-paddy fields was obtained from the results of overlapping maps of Pallangga District land use maps in 2005 and 2016 and presented in the form of cross tabulations. The accuracy test results obtained the overall accuracy value of 98.04%, and the kappa accuracy value of 0.98. This study shows that paddy field area has decreased by 305.25 ha. The change consisted of 17.68 ha into a water body, turned into a garden of 132.86 ha and became a settlement of 154.71 ha. The conversion of paddy fields in Pallangga District in 2005-2016 affected rice production. The results of the analysis of the needs of rice per capita per year show that in 2017 Pallangga District is surplus in the supply of rice to its population. However, based on population projection, the decrease in land area and rice production in Pallangga Subdistrict in 2020 was unable to meet the rice needs of its population of 1,027 tons